The politics of pests: immigration and the invasive other - Anderson, B (John Hopkins University Press, 2017)
In 2015 more than one million people entered the European Union, many fleeing wars in the Middle East. There was a strand of hostile media coverage that represented migrants as vermin or insects. This paper examines the context of this representation and argues that that association of vermin – waste, numbers and threats to the home –provides useful insights into the anxieties underpinning negative responses to asylum seekers. Analysing these representations offers insights into the kinds of political questions that must be tackled in struggling for more positive responses.